Riemannian structure and flows for smooth geometric image labeling - Savarino, Fabrizio; Schnörr, Christoph (Proceedings in applied mathematics and mechanics, 2019)
The image labeling problem can be described as assigning to each pixel a single element from a finite set of predefined labels. Recently, a smooth geometric approach for inferring such label assignments was proposed by following the Riemannian gradient flow of a given objective function on the so‐called assignment manifold.